Attitude toward Virtual Communion in Relation to Church Tradition during the COVID-19 Pandemic in the United Kingdom - Village, Andrew (Journal of empirical theology, 2022)
Attitude toward virtual communion was assessed among 3,300 Roman Catholic, Anglican, and Free Church clergy and laity during the COVID-19 pandemic in the UK in 2021. A six-item unidimensional scale (Scale of Attitude Toward Virtual Communion, SATVC) assessed attitude related to receiving communion during online services, the necessity of priests for consecration and lay presidency of communion at home. Church tradition predicted attitude in ways that were in line with historical understandings of the Eucharist and ecclesial debates about the necessity of priests to preside over ritual. Within traditions, other factors operated in different ways, producing a complex web of interactions. Older people were more positive about virtual communion than younger ones, but mainly in Catholic traditions. Clergy were more negative in most traditions except Free Church. Having a generally conservative doctrinal stance drove Catholic and Reformed traditions in opposite directions. Liturgical stance predicted SATVC independently of doctrinal stance, and more traditional stance tended to lead to more uniformity, rather than divergence, between traditions.